STABILITY ANALYSIS FOR YIELD AND RELATED TRAITS IN PEARL MILLET (Pennisetum glaucum (L.) R. Br.) HYBRIDS - G. SANYO SARA, R. NIRMAL RAJ, J. GOKULAKRISHNAN and M. PRAKASH* (The Journal of Research ANGRAU, 2022)
Stability analysis for thirty-three pearl millet genotypes and two checks was carriedout in three different environments during 2018-2019. G × E interaction was estimated using Eberhartand Russell model and genotype-grouping method. The ANOVA revealed significant effect ofenvironments on the performance of hybrids for the three traits taken. Among the hybrids, AUBH-15showed stable performance for grain yield per plant as it had high mean, non-significant deviationfrom regression (S2di), regression around unity and low co-efficient of variation, hence, this hybridcan be recommended for commercial cultivation. The hybrids which were identified as stable forother attributing traits by regression model could not be confirmed by the grouping technique. Thus, therecommendation was given based on the grain yield per plant, the most important economic trait. Thestudy must be extended to more diverse testing sites to obtain more robust information on theenvironment effect.